Digital Literacy Level and English Language Proficiency of College Students in Banjarmasin to Support Independent Learning Campus in the Technological Era 4.0 - Isnaniah Isnaniah; Rahma Pitria Ningsih (English Department of Faculty of Tarbiyah and Teacher Training, 2022)
In this digital era, it is essential for individuals to be literate and to be able to communicate effectively in English as the international language. Foreign language proficiency certainly requires training which the process itself cannot be achieved instantly. Since the beginning of college, students should begin to know and be trained to understand and utilize English. Therefore, it is crucial to employ English as a second language in the classroom so that students can meet the challenges of the globalization era in the future. This research aims to analyze the level of digital literacy and the distribution of students' English skills in the City of Banjarmasin in supporting the readiness of independent campuses to learn in the technology era 4.0. This research effort employs exploratory questionnaires as its methodological technique (exploratory research). The analysis was performed using simple regression. According to the finding of the research, it illustrates that the distribution of digital literacy levels and the distribution of students' English skills in Banjarmasin is almost evenly distributed.In this digital era, it is essential for individuals to be literate and to be able to communicate effectively in English as the international language. Foreign language proficiency certainly requires training which the process itself cannot be achieved instantly. Since the beginning of college, students should begin to know and be trained to understand and utilize English. Therefore, it is crucial to employ English as a second language in the classroom so that students can meet the challenges of the globalization era in the future. This research aims to analyze the level of digital literacy and the distribution of students' English skills in the City of Banjarmasin in supporting the readiness of independent campuses to learn in the technology era 4.0. This research effort employs exploratory questionnaires as its methodological technique (exploratory research). The analysis was performed using simple regression. According to the finding of the research, it illustrates that the distribution of digital literacy levels and the distribution of students' English skills in Banjarmasin is almost evenly distributed.